A randomized controlled trial testing the effectiveness of a universal school-based depression prevention program 'Op Volle Kracht' in the Netherlands - Tak Yuli R; Van Zundert Rinka MP; Kuijpers Rowella CWM; Van Vlokhoven Boukje S; Rensink Hettie FW; Engels Rutger CME (BMC, 2012)
Abstract Background The incidence of depressive symptoms increases during adolescence, from 10.0% to 24.5% at age 11 to 15, respectively. Experiencing elevated levels of depressive symptoms increases the risk of a depressive disorder in adulthood. A universal school-based depression prevention program Op Volle Kracht (OVK) was developed, based on the Penn Resiliency Program, aimed at preventing the increase of depressive symptoms during adolescence and enhancing positive development. In this study the effectiveness of OVK will be tested and possible mediators of program effects will be focus of study as well. Method The effectiveness of OVK will be tested in a randomized controlled trial with two conditions, intervention (OVK) and control condition (care as usual). Schools are randomly assigned to research conditions. OVK will be incorporated in the school curriculum, maximizing program attendance. OVK consists of 16 lessons of 50 min, given by trained psychologists to groups of 11-15 students. OVK contains Cognitive Behavioral Therapy, social skills training, problem solving and decision making. Outcomes are measured at 6, 12, 18 and 24 months follow up, to monitor long term program effects. Primary outcome is level of depressive symptoms, secondary outcomes are: anxiety, hopelessness, cognitive bias, substance use, truancy, life satisfaction, coping, self-efficacy, optimism, happiness, friendship, school performance and school attitude. The questionnaires for students will be administered in the school setting. Parents will complete a questionnaire at baseline only. Discussion In this paper the study into the effectiveness of the depression prevention program OVK was described. It is expected that OVK will prevent the increase in depressive symptoms during adolescence and enhance positive development in the intervention condition, compared to the control condition. If OVK will be effective, it can be implemented in the school context by which numerous adolescents can be reached. Trial registration Netherlands Trial Register (NTR): NTR2879